The Concept of Innovative Projects Evaluation in the Company - Jan SIEKIERSKI; Witold ZYCH (Communications of International Proceedings, 2021)
The aim of the article is to present the concept of an innovative project evaluation system in an enterprise and to present the results of empirical research. A thesis, confirmed in the practice of the researched enterprise, that efficient operation of the innovative project evaluation system is of paramount importance in the innovative activity of enterprises has been adopted.  The article has a theoretical and empirical character. A functional approach was accepted in the study. In order to achieve the objective and to verify the theses, the following research methods were used: literature analysis, expert research, analysis of impact factors, desk research, moreover, a questionnaire was used as a method of empirical data collection. The set of features (criteria) of the innovative project evaluation system was extracted during the two-phase research. In the first phase of the analysis, 27 evaluation criteria were established, including 3 main criteria and 24 partial criteria. In the second phase of the research, the significance of the criteria of the innovative project evaluation system was analysed on the basis of the respondents' indications. Three main criteria were selected: feasibility, functionality and effectiveness, which were each assigned 3 sub-criteria. Verification of the innovative project evaluation system was carried out during the evaluation of the innovative project of the studied Company. The analysis shows that the properties of the main and partial criteria, as the nodal elements of the innovation project evaluation system, fulfil the diagnostic and developmental function of the enterprise. In particular, it was found that the innovation project evaluation system is an important tool for dynamizing the innovation process, increasing the efficiency of the innovation project, increasing the productivity and competitiveness of the enterprise.
Keywords: Innovation; Innovative Project; Innovative Project Evaluation System; Competitiveness.